Iliac trabecular bone formation predicts radial trabecular bone density changes in type 1 osteoporosis. - Hesp, R; Arlot, M; Edouard, C; Bradbeer, J; Meunier, P; Reeve, J (1991)
In 28 patients with idiopathic or postmenopausal type 1 (spinal crush fracture) osteoporosis, resorption indices and dynamic measurements of trabecular bone formation based on in vivo tetracycline labeling in 7.5 mm transiliac biopsies have been compared with trends in radial cortical and trabecular bone density measured with computed tomography. Positive correlations were observed between trabecular bone density trends in the radius and indices of bone formation in the ilium. These were improved when one of the two resorption indices was included with a formation index in bivariate regressions. Marked interindividual variations in radial bone density trends were also seen in cortical bone. These correlated poorly with trends in trabecular bone. Weak negative relationships between cortical bone trends and indices relating to bone formation and resorption were observed, but a positive association was seen with single-labeled surfaces on iliac trabeculae. If, as has been suggested, there are periodic variations in bone formation, the results suggest that axial and peripheral trabecular bone density trends are synchronized in osteoporosis, perhaps in response to systemic factors, such as circulating hormones.